1995
DOI: 10.1007/bf02576768
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prior portosystemic shunt on early hepatic hemodynamics and sinusoids following 84% hepatectomy in dogs

Abstract: The effects of a prior portosystemic shunt (PSS) on the hepatic hemodynamics and sinusoids shortly after an 84% hepatectomy (Hx) were investigated in dogs. Fifteen mongrel dogs were divided into three groups, a 70% Hx group (n = 5), an 84% Hx group (n = 5) and an 84% Hx+PSS group (n = 5). In the last group, a shunt was inserted between the splenic and femoral veins prior to the hepatectomy. The systemic and hepatic hemodynamics were measured, before and 180 min after the hepatectomy, and the remaining liver ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 24 publications
0
25
0
1
Order By: Relevance
“…In recent years, growing evidence has been gained that postoperative recovery following extended partial hepatectomy is indeed not only a question of remnant liver mass, but also a question of microcirculation in the remnant liver parenchyma [1,7,18,19] . In this context, studies from living-related liver transplantation have reported that an increase of portal venous blood fl ow occurring if splanchnic venous blood running through reduced-size livers may positively infl uence hepatocellular regeneration and liver mass restoration [18,19] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, growing evidence has been gained that postoperative recovery following extended partial hepatectomy is indeed not only a question of remnant liver mass, but also a question of microcirculation in the remnant liver parenchyma [1,7,18,19] . In this context, studies from living-related liver transplantation have reported that an increase of portal venous blood fl ow occurring if splanchnic venous blood running through reduced-size livers may positively infl uence hepatocellular regeneration and liver mass restoration [18,19] .…”
Section: Discussionmentioning
confidence: 99%
“…These animals experienced lower AST levels (421 8 36 vs. 574 8 73 U/l) Beside size matching in the transplant situation [6] , other strategies have been described to reduce portal blood fl ow and to overcome postoperative portal hyperperfusion in small-for-size livers following extended liver resection. In this context, it was reported that the presence of a portosystemic (portocaval) shunt effectively diminished portal venous pressure resulting in increased survival rates in animal studies [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…The relative portal hyperperfusion, even in the setting of complete liver grafts, is only partially due to hyperdynamic splanchnic circulation in ESLD (22). Extensive hepatectomy in dogs leads to higher portal pressure and higher sinusoidal resistance as the portal flow is directed through a small remnant liver (24). Similarly, after partial liver transplantation the graft is subjected to the portal flow destined for a whole liver, so post-transplant hyperperfusion is more pronounced than in whole liver grafts.…”
Section: Vascular Inflowmentioning
confidence: 99%
“…The observation of the fact that a graft weight/body weight ratio <0.8% predisposes to SFSS has resulted in the assumption that portal hyperperfusion is the main culprit as the flow per gram liver tissue through the liver sinusoids increases to a harmful level. Evidence that this is the case is seen in preclinical large-animal models with portal vein decompression by portosystemic shunting in transplantation of small-for-size grafts [50,51,52,53,54,55] and in combined models of hepatectomy with marginal liver remnants and portosystemic shunting [56,57]. Portal vein decompression, a normalization of the portal vein pressure and portal flow improves liver regeneration.…”
Section: Quality Versus Quantity – the Conflict Between The Flow And mentioning
confidence: 99%